2006
DOI: 10.1111/j.1365-2958.2006.05203.x
|View full text |Cite
|
Sign up to set email alerts
|

Portal fusion protein constraints on function in DNA packaging of bacteriophage T4

Abstract: Architecturally conserved viral portal dodecamers are central to capsid assembly and DNA packaging. To examine bacteriophage T4 portal functions, we constructed, expressed and assembled portal gene 20 fusion proteins. C-terminally fused (gp20-GFP, gp20-HOC) and N-terminally fused (GFP-gp20 and HOC-gp20) portal fusion proteins assembled in vivo into active phage. Phage assembled C-terminal fusion proteins were inaccessible to trypsin whereas assembled N-terminal fusions were accessible to trypsin, consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 44 publications
(82 reference statements)
2
107
0
Order By: Relevance
“…These bases either are part of, or flank, the intermolecular pseudoknot. Additionally, the ability to simultaneously align both connectors and pRNAs when one is averaging over thousands of particles indicates that the relative orientations of these two components are fixed and that thus, the connector has a preferred orientation and is not free to rotate, in agreement with the findings of biochemical and single-particle experiments (51,52). If this were not the case, it would be impossible to simultaneously align both components unless different angular orientations were applied to subimage areas corresponding to connectors and pRNAs during image reconstruction (see reference 20 for further discussion).…”
Section: Resultssupporting
confidence: 78%
“…These bases either are part of, or flank, the intermolecular pseudoknot. Additionally, the ability to simultaneously align both connectors and pRNAs when one is averaging over thousands of particles indicates that the relative orientations of these two components are fixed and that thus, the connector has a preferred orientation and is not free to rotate, in agreement with the findings of biochemical and single-particle experiments (51,52). If this were not the case, it would be impossible to simultaneously align both components unless different angular orientations were applied to subimage areas corresponding to connectors and pRNAs during image reconstruction (see reference 20 for further discussion).…”
Section: Resultssupporting
confidence: 78%
“…The precession, if unidirectional, would produce less twist than would be produced by the previously proposed portal rotation that tracks the DNA double helix (34,39). Portal rotation is now known not to occur (40,41). Finally, the core stack precession could be a response to evolutionary selection against tangling of DNA as it was packaged.…”
Section: T7 Portal Vertex Layers Lack Long-range Correlation In Theirmentioning
confidence: 97%
“…In the early models of genome packaging, the DNA translocation was assumed to be coupled with the portal rotation. 59,61 However later single-molecule fluorescence spectroscopy of the φ29 portal 62 and studies of the T4 connector non-covalently cross-linked to the capsid shell 63 showed that the portal does not rotate during the DNA translocation.…”
Section: Capsid Assemblymentioning
confidence: 99%